A simple FRET system using two‐color CdTe quantum dots assisted by cetyltrimethylammonium bromide and its application to Hg(II) detection. (24th January 2019) - Wang, Jing; Song, Fengjuan; Ai, Yongling; Hu, Shanwen; Huang, Zhizhou; Zhong, Wenying
Abstract: In this study, we developed a novel simple fluorescence resonance‐energy transfer (FRET) system between two‐color CdTe quantum dots (QDs) assisted by cetyltrimethylammonium bromide (CTAB). Mercaptopropionic (MPA)‐capped CdTe QDs serving as both donors and acceptors were successfully synthesized by changing the refluxing time in aqueous solution. CTAB micelles formed in water and minimized the distance between the donors and acceptors significantly by electrostatic interactions, improving FRET efficiency. Several factors that affected the fluorescence spectra of the FRET system were investigated. The prepared FRET system was feasible as an effective fluorescent probe to detect Hg(II) in aqueous solution. At pH 7.0, a linear relationship between the quenched fluorescence intensity of orange‐emitting acceptors (QDs(A) ) and Hg(II) concentration was acquired in the range 5–250 nmol/L with a detection limit of 1.95 nmol/L. The developed method showed excellent analytical performance for Hg(II) with high sensitivity and acceptable selectivity, reproducibility and stability. This finding indicated that the method has a promising potential application for environmental monitoring. This study demonstrated the great promise of QDs for expedient, low‐cost and high‐sensitivity detection of Hg(II).